Manejo integrado de mancha angular (Phaeoisariopsis griseola) en cultivos de frejol (Phaseolus vulgaris) - Santillán Espinoza, Jonathan Alexander (2024)
In reference to the study, the objective has been set; describe the integrated management of angular spot (Phaeoisariopsis griseola) in bean (Phaseolus vulgaris) crops. Based on the methodology, the proposed research is framed within the qualitative approach, this approach allows exploring the experiences, perceptions and contexts that surround this topic. In results, the identification of the severity caused by angular spot in bean crops is essential to understand and effectively address this problem. Firstly, the direct impact on the particularity and interest of the crops is highlighted, since the presence Angular spot can result in a significant decrease in bean production. In conclusion, the evaluation of the severity caused by angular spot in bean crops highlights its significant impact on production; this disease, caused by the fungus Phaeoisariopsis griseola, can result in substantial losses in yield and quality of beans.